Physiological and morphological responses of two beans common genotype to water stress at different phenological stages (Bioscience Journal, 2023)
Comprehension of the bean responses of beans common under to water deficit is an important tool in agricultural planning, like sowing time, and deficit irrigation management strategies. The study aimed to understand the morpho-physiological responses and yield attributes of two common bean genotypes submitted to water stress at different phenological stages. The study was carried out in a greenhouse, in randomized block scheme with five repetitions. To achieve the objectives deficit irrigation of 25% of crop evapotranspiration was practiced during vegetative (DI-V), flowering (DI-F), and pod filling (DI-PF) stages. A non-deficit irrigated (NDI) and deficit irrigated through vegetative to pod filling stages (DI-VP) treatments were added for comparison. The following morphophysiological responses and yield attributes were evaluated: net assimilation of CO2, stomatal conductance, and leaf transpiration, chlorophyll index, number of trifoliate leaves, chlorophyll index, leaf area, number of grains per plant, number of grains per pod, number of pods per plant, the mass of thousand grains, harvest index, and water use efficiency. The beans genotype under DI-V exhibited acclimation, observed by the relative increment with NDI of 195%, 759%, and 231% of net assimilation of CO2, stomatal conductance, and leaf transpiration, respectively. Plants under treatment DI-PF experienced dis-stress and plastic responses as leaf losses and exhaustion of gas exchanges. Treatment DI-V received 11% less water than NDI and exhibited equal yield, resulting in higher water use efficiency. Yield attributes correlations indicated that yield penalty might be related to pods abortion, which not occurred to plants under DI-V.